Macronutrient absorption curves of carrot in the high tropics - Fernández-Pérez, Carlos Julio; Cely-Reyes, Germán Eduardo; Serrano-Cely, Pablo Antonio (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2023)
Carrot cultivation in Colombia reached 9,000 hectares in 2020. The production chain of this crop faces various problems, among which marketing and nutrition stand out, the latter a decisive factor for performance. Some studies claim that with the use of hybrids in combination with irrigation and balanced fertilization, yields greater than 70 t ha-1 can be obtained. The commercial competitiveness of crops is related to the timely, adequate and efficient application of nutrients; element absorption curves are tools that offer effective information on how much the crop assimilates during its phenological cycle, allowing us to know the minimum required amount of elements for the specific area. A carrot crop was established to determine the foliar absorption curves of macronutrients (N, P, K, Mg and Ca). The yield obtained was 39.6 t ha-1, with 552,500 plants/ha. K was the element with the highest absorption 147 days after sowing with 29.36 kg ha-1 for the leaves and 27.74 kg ha-1 in the root and a total of 57.1 kg ha-1. The order of the other elements was N, Ca, P and Mg. This information is useful for managing carrot nutrition in order to make fertilizer management efficient and improve yield.